Use of a sparse sampling study design to assess transfer of tramadol and its O-desmethyl metabolite into transitional breast milk - Ilett, Kenneth F (Blackwell Science Inc, 2008)
AIMS: To investigate the transfer of rac-tramadol and its rac-O-desmethyl metabolite into transitional milk, and assess unwanted effects in the breastfed infant. METHODS: Tramadol HCl (100 mg six hourly) was administered to 75 breastfeeding mothers for postoperative analgesia on days 2–4 after Caesarian section. Milk and plasma samples were collected after administration of four or more doses. Rac-tramadol and rac-O-desmethyltramadol were measured by high performance liquid chromatography. Milk : plasma ratio (M : P) and infant doses were calculated by standard methods. The behavioural characteristics of the exposed breastfed infants and a matched control group of infants not exposed to tramadol were also studied. RESULTS: At steady-state, mean (95% CI) M : P was 2.2 (2.0, 2.4) for rac-tramadol and 2.8 (2.5, 3.1) for rac-O-desmethyltramadol. The estimated absolute and relative infant doses were 112 (102, 122) μg kg(−1) day(−1) and 30 (28, 32) μg kg(−1) day(−1), and 2.24% (2.04, 2.44)% and 0.64% (0.59, 0.69)% for rac-tramadol and rac-O-desmethyltramadol, respectively. The exposed infants and control breastfed infants had similar characteristics, including Apgar scores at birth and Neurologic and Adaptive Capacity Scores. CONCLUSIONS: The combined relative infant dose of 2.88% at steady-state was low. The similarity of NACS in exposed infants and controls suggests that there were no significant behavioural adverse effects. We conclude that short-term maternal use of tramadol during establishment of lactation is compatible with breastfeeding.